2020
DOI: 10.1016/j.celrep.2019.12.010
|View full text |Cite
|
Sign up to set email alerts
|

SETDB1-Mediated Cell Fate Transition between 2C-Like and Pluripotent States

Abstract: Highlights d Setdb1-KO fails to induce trophectoderm (TE) differentiation in ''ground-state'' ESCs d Setdb1 deficiency initiates 2C-like transition program in a Dux-dependent manner d Nanog overexpression suppresses 2C-like transition induced by Setdb1-KO d The ''ground-state'' Setdb1-null ESCs undergo necroptosis by activating Ripk3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 70 publications
2
63
0
Order By: Relevance
“…6f ). Furthermore, many E2F6-repressed germline genes are overexpressed upon SETDB1 inactivation in ESCs in 2i or serum conditions 48 , 49 (Supplementary Fig. 6a, b ).…”
Section: Resultsmentioning
confidence: 96%
“…6f ). Furthermore, many E2F6-repressed germline genes are overexpressed upon SETDB1 inactivation in ESCs in 2i or serum conditions 48 , 49 (Supplementary Fig. 6a, b ).…”
Section: Resultsmentioning
confidence: 96%
“…Deletion of LSD/KDM1A leads to an increase of H3K4me2/me3 and H3K27ac, and decrease of H3K9me/me2, as well as expanded fate potential in mESCs ( Macfarlan et al., 2011 ). Loss of SETDB1, the methyltransferase of H3K9me3, initiates a 2-cell-like transition program by inducing the expression of DUX in mESCs ( Wu et al., 2020 ). Conversely, the restoration of repressive marks may restrict cell fate among distinct lineages.…”
Section: Main Textmentioning
confidence: 99%
“…Over the last decade, several epigenetic factors activating or inhibiting the 2CLC state have been identified (Iturbide & Torres-Padilla, 2020), including non-coding RNAs (Choi et al, 2017; Percharde et al, 2018; Yang et al, 2020).Several known negative regulators of the 2CLC state were present among the top hits of the DASH screen.For instance, the SUMO E3-ligase PIAS4 ranked #41(Yan et al, 2019); the chromatin-remodeler p400 ranked #52(Rodriguez-Terrones et al, 2018); the histone demethylase LSD1 ranked #111(Macfarlan et al, 2012); the ncPRC1 subunits RING1B and RYBP ranked #100 and #245 respectively (Rodriguez-Terrones et al, 2018). However, many of the previously known 2CLC epigenetic regulators such as histone chaperone CAF-1(Ishiuchi et al, 2015), transcription factor TRIM28 (De Iaco et al, 2017), the H3K9 methyltransferase SETDB1(Wu et al, 2020), and the m6 A binding protein YTHDC1(Liu et al, 2021) were not ranked high in our screen. This could be due to the lethality associated with these KOs, especially considering the timeline of the DASH screen(3 weeks) in comparison to siRNA screens (Rodriguez-Terrones et al, 2018) with short timelines, where these factors were identified.…”
mentioning
confidence: 78%
“…Rodriguez-Terrones et al, 2018); the histone demethylase LSD1 ranked #111(Macfarlan et al, 2012); the ncPRC1 subunits RING1B and RYBP ranked #100 and #245 respectively (Rodriguez-Terrones et al, 2018). However, many of the previously known 2CLC epigenetic regulators such as histone chaperone CAF-1(Ishiuchi et al, 2015), transcription factor TRIM28(De Iaco et al, 2017), the H3K9 methyltransferase SETDB1(Wu et al, 2020), and the m6 A binding protein YTHDC1(Liu et al, 2021) were not ranked high in our screen. This could be due to the lethality associated with these KOs, especially considering the timeline of the DASH screen(3 weeks) in comparison to siRNA screens (Rodriguez-Terrones et al, 2018) with short timelines, where these factors were identified.…”
mentioning
confidence: 80%